Catching our breath: reshaping rehabilitation services for COVID-19. Issue 1 (2nd January 2021) - Khoo, Teng Cheng; Jesudason, Edwin; FitzGerald, Alasdair
Abstract: Purpose: War and natural disaster have been spurs to the creation of rehabilitation services. The COVID-19 pandemic poses a different question for existing rehabilitation services: how best to respond to a disaster that is anticipated from afar, but whose shape has yet to take full form? Methods: Applying the 5-phase crisis management model of Pearson and Mitroff, we report our experience at one of Scotland's largest centres for rehabilitation, in planning to cope with COVID-19. Results: Contingency rehabilitation planning can be framed in a 5-phase crisis management model that includes (i) signal detection; (ii) prevention/preparedness; (iii) damage limitation; (iv) recovery; and (v) learning. We have reported the impact of COVID-19 on rehabilitation services within a Scottish context and shared some of our learning. Conclusion: COVID-19 has challenged healthcare worldwide and has served as an amplifier for the recognised ill effects of poverty and inequality. As rehabilitation clinicians, we are in a position to continue advocating for people facing disability, and also seeking and responding to signals of COVID-19's late effects in both COVID-19 and non-COVID-19 patients alike. IMPLICATIONS FOR REHABILITATION: COVID-19 has resulted in unprecedented challenges in rehabilitation service planning. Contingency rehabilitation planning can be framed in a 5-phase crisis management model of Pearson and Mitroff, including (i) signal detection; (ii) prevention/preparedness; (iii) damage limitation; (iv) recovery; and (v) learning. COVID-19 has served as an amplifier for the recognised ill effects of poverty and inequality; as rehabilitation clinicians, we are in a position to continue advocating for people facing disability, and also seeking and responding to signals of COVID-19's late effects in both COVID-19 and non-COVID-19 patients alike.